A Further Study on Knoop Indentation Plastic Deformation for Evaluating Residual Stress - Kim, Woojoo; Lee, Kyungyul; Kim, Jong-hyoung; Kim, Young-Cheon; Kwon, Dongil (Korean Journal of Metals and Materials, 2020)
A method for evaluating residual stress using an instrumented indentation test was developed some decades ago. More recently, another method was developed, using a Knoop indenter. The conversion factor ratio, which is one of the key factors in the evaluation algorithm, has been taken to be 0.34, although this value comes from an experimental result and its physical meaning has not been examined. Here we examine the physical meaning of this conversion factor from the previous residual stress model, and calculate its ratio using analytical model of the stress field beneath the indenter. In this process, we assumed that the conversion factor ratio was the ratio of the projected area of the plastic zone generated during the Knoop indentation test. An analysis of the stress field beneath the indenter was performed by FE simulation. Actual nanoindentation was conducted after Knoop indentation testing, using the interface-bonding technique, to identify the plastic zone. In addition, the conversion factor ratio was also calculated for the case where residual stress was present, and the geometric ratio of the Knoop indenter was different. A comparison of our results with those from previous studies showed that the conversion factor ratio obtained using our assumption was in good agreement with previous studies.